Comparison of Brilliant Blue G and Trypan Blue during Vitrectomy for Macular Hole Surgery - Muhammad Shaheer, Chaudhary Nasir Ahmad (Pakistan Journal of Ophthalmology, 2014)
Purpose: To compare the ease in internal limiting membrane peeling with the use of trypan blue and brilliant blue G. Material and Methods: This comparative cross sectional study was conducted at Eye Unit III, over duration of two years 1st March 2012 to 28th February 2014, Institute of ophthalmology, Mayo Hospital, Lahore. patients with stage three and four age related macular hole were included in study. They were divided into two groups of thirty patients each. Group A patients underwent internal limiting membrane peeling with the use of brilliant blue G while group B patients underwent internal limiting membrane peeling with adjunctive trypan blue. Results: The internal limiting membrane peeling was done in of patients in first bite in brilliant blue G group. While only patient underwent successful internal limiting membrane peeling in first bite in the trypan blue group. The internal limiting membrane peeling was done in less than three minutes in patients in brilliant blue G group as compared to in trypan blue group. Collateral damage occurred in patients in trypan blue group as compared to patient only in brilliant blue Group. Conclusion: Brilliant blue G is the a more useful dye than trypan blue in internal limiting membrane peeling in terms of staining, ease of peel and less side effects. Key Words: Brilliant blue G, Macular Hole, Vitrectomy,